Macromedia Flash 8 on demand - Anderson, Andy (Que, 2005)
If you are looking for a fast, visual way to learn Macromedia Flash 8 and create your interactive website, Macromedia Flash 8 On Demand is the book you need. Step-by-step instructions with accompanying 4-color visuals mean you'll spend less time reading and more time learning. You'll learn how you can easily integrate and add interactivity with tools, develop content using pre-built components and effectively improve authoring capabilities with custom extensions. The new features icon used throughout the book highlights what's new in Macromedia Flash 8 and a troubleshooting guide is included to help solve your most common problems. Also, the companion software shows you how to perform everyday tasks and helps you gain web authoring experience. Let Macromedia Flash 8 On Demand help you master Macromedia Flash 8.